50세 이상 중년 및 노인의 건강행위 요인에 따른 영양위험 연구 - 임경숙(Kyeong Sook Yim) (Korean journal of community nutrition, 2007)
Undernutrition could be a significant deterrent to healthy aging and could negatively affect health outcomes in elderly. This study aimed to assess health-related factors which are associated with nutritional risks in middle-aged and elderly individuals by a cross-sectional study. Interviews were conducted with 2660 subjects (847 males, 1813 females), aged 50 years and over, in 15 cities in Korea. Data on food intake were obtained through a validated semi-quantitative food frequency questionnaires. Nutritional status were analyzed according to health-related factors including cigarette smoking, alcohol drinking, exercise, stress and depression level. Less regular exercise was associated with a higher likelihood of a poor nutrition [odds ratio (OR) 1.94; 95% confidence intervals (CI) 1.43-2.65] of middle-aged and elderly male subjects. Cigarette smoking (OR 1.84; 95% CI 1.24-2.71), less exercise (OR 2.58; 95% CI 2.07-3.21), stress (OR 1.73; 95% CI 1.36-2.22), and depression (OR 1.34, 95% CI 1.08-1.67) of middle-aged and elderly female subjects was associated with a higher likelihood of a poor nutrition. The results of the multiple regression analysis showed that less exercise proved to be the strongest predictors for the poor nutrition, followed by stress, smoking, and depression (model $R^2= 9.0%$). It suggests that guidance to promote regular exercise, to quit smoking, to minimize stress and depression level might help to improve nutritional status of middle-aged and elderly in Korea. These findings also suggest that having recommendable health behaviors are beneficial to the good nutrition of subjects aged 50 years and over.